Kr-h1, a Cornerstone Gene in Insect Life History - He, Qianyu; Zhang, Yuanxi (Frontiers in Physiology, 2022)
Insect life cycle is coordinated by hormones and their downstream effectors. Krüppel homolog1 (Kr-h1) is one of the crucial effectors which mediates the actions of the two critical hormones of insects, the juvenile hormone (JH) and 20-hydroxyecdysone (20E). It is a transcription factor with a DNA-binding motif of eight C2H2 zinc fingers which is found to be conserved among insect orders. The expression of Kr-h1 is fluctuant during insect development with high abundance in juvenile instars and lower levels in the final instar and pupal stage, and reappearance in adults, which is governed by the coordination of JH, 20E, and miRNAs. The dynamic expression pattern of Kr-h1 is closely linked to its function in the entire life of insects. Over the past several years, accumulating studies have advanced our understanding of the role of Kr-h1 during insect development. It acts as a universal antimetamorphic factor in both hemimetabolous and holometabolous species by directly inhibiting the transcription of 20E signaling genes Broad-Complex (Br-C) and Ecdysone induced protein 93F (E93), and steroidogenic enzyme genes involved in ecdysone biosynthesis. Meanwhile, it promotes vitellogenesis and ovarian development in the majority of studied insects. In addition, Kr-h1 regulates insect behavioral plasticity and caste identity, neuronal morphogenesis, as well as maturation of sexual behavior. Hence, Kr-h1 acts as a master regulator in insect life.